STRESS IN THE ELDERLY IN THE CONTEXT OF THE COVID-19 PANDEMIC AND ITS ASSOCIATED FACTORS - Arpasi-Quispe, Orfelina; Fernandez-Molocho, Lili; Mocarro-Aguilar, Maria Rosario; Díaz-Orihuela, Maria Magdalena; Fhon, Jack Roberto Silva (Cogitare Enfermagem, 2023)
Objective: To identify stress in the elderly living in the city of Lima and its association with demographic factors, infodemics, the presence of physical and psychological symptoms, and the use of illicit substances in the context of the Covid-19 pandemic. Method: Quantitative, transversal, and analytical study through the web-based survey with 384 elderly from the city of Lima - Peru between April and August 2021. The instruments of demographic profile, Perceived Stress Scale, and self-reported symptoms were used for the study. The Multiple logistic regression was used, considering the significance level of 5%. Results: 62% were women, and the age ranged between 60 and 95 years with a mean of 70.5. The stress average was 26.8 points. Stress was associated with fear of relatives dying and concern for the elderly. Conclusions: it is important for health professionals trained to identify changes in mood in the elderly and to create individualized care plans.